(3hXGFa GdeOjQs - (3RjO efjQ(B, (3YHhjs ((3YeGf(B:s (3OGQ MLdI(B,s, 2007)
(3jYQV gPG GdcJGH aj WjGJg eGjdj (B: (3eONd Edi GdGOGQI , hXGFa GdGOGQI , GdGOGQI GdeYGUQI GdMOjKI , YhGed fLGM GdGOGQI aj Xd aj GdXQha GdeJZjQI , CgejI ENJjGQ GdeOjQ GdefGSH , GdJLOjO hGdGUdGM aj GdbjGOI GdGOGQjI ddeDSSGJ , JfejI GdbOQGJ GdGOGQjI , JYQja GdQDjG hJhKjbgG aj NOeI GdaMhi , GdGOGQI hGdMcheI GdGdcJQhfjI , GOGQI GdeYQaI hOhQgG aj GQSGA JLeY GdeYdheGJ , GdgfOQI s
(3HjHdjhZQGaj U(B. 263s
Keywords: (3GdQDSGA h GdeOjQhfs; (3GdbjGOI GdEOGQjIs